Stereoconvergent Approach to the Enantioselective Construction of α‐Quaternary Alcohols by Radical Epoxide Allylation - Höthker, Sebastian; Plato, Annika; Grimme, Stefan; Qu, Zheng‐Wang; Gansäuer, Andreas (Angewandte Chemie International Edition, 2024)
We describe a highly stereoconvergent radical epoxide allylation towards diastereomerically and enantiomerically enriched α‐quaternary alcohols in two steps from olefins. Our approach combines the stereospecifity and enantioselectivity of the Shi epoxidation with the unprecedented Ti(III)‐promoted intramolecular radical group transfer allylation of epoxides. A directional isomerization step via configurationally labile radical intermediates enables the selective preparation of all‐carbon quaternary stereocenters in a unique fashion. We demonstrate an operationally simple approach towards α‐quaternary alcohols in good to excellent diastereomeric and enantiomeric ratios in two steps from diastereomeric mixtures of trisubstituted olefins. Our method relies on an unprecedented, radical, intramolecular syn‐allyl transfer to intermediate β‐titanoxy radicals resulting from an Cp2TiIIIallyl‐induced fragmentation of epoxide precursors.